The Cabinet of Earths - Nesbet, Anne (Harper, 2012)
Thirteen-year-old Maya, in Paris with her family for a year, lands in the middle of the mysterious La Societé's quest for immortality when the magical Cabinet of Earths chooses her as its next Keeper, promising to restore her mother's health. Includes historical notes.